2020
DOI: 10.1177/0954407020959895
|View full text |Cite
|
Sign up to set email alerts
|

Influence of braking on dynamic stability of car-trailer combinations

Abstract: The influence of braking on dynamic stability of a car-trailer combination (CTC) is studied in this paper. The braking is simply modeled and integrated into a single-track model (STM) with a single-axle trailer. On this basis, some fundamentals and analysis results related to system dynamic stability are given through simulation. Furthermore, it is found that the axle load transfer and braking force distribution have a great influence on system dynamic stability. In order to further analyze the influence of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…With the help of ASC, it was possible to optionally change the radial reactions of the vehicle wheels and thus their adhesion [31]. The auxiliary wheels of the alternative SkidCar system were free to rotate around the vertical axis, so they did not lead the vehicle, but only transmitted vertical forces.…”
Section: Methodsmentioning
confidence: 99%
“…With the help of ASC, it was possible to optionally change the radial reactions of the vehicle wheels and thus their adhesion [31]. The auxiliary wheels of the alternative SkidCar system were free to rotate around the vertical axis, so they did not lead the vehicle, but only transmitted vertical forces.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, the equivalent rotation angle d y of the rack displacement to the kingpin can be further expressed as equation (12).…”
Section: Modeling Of the Full Vehiclementioning
confidence: 99%
“…The simulation results showed that the stability of the CTC depended largely on the damping at the hitch point when braking, but excessive damping was not conducive to the suppression of body sway. Zhang et al 12,13 also had a series of work on the dynamic stability of CTC. He proposed a parameter identification method based on time-frequency analysis for time-varying vehicle dynamics.…”
Section: Introductionmentioning
confidence: 99%